2014
DOI: 10.1371/journal.pone.0105704
|View full text |Cite
|
Sign up to set email alerts
|

Central and Systemic Responses to Methionine-Induced Hyperhomocysteinemia in Mice

Abstract: Hyperhomocysteinemia has been considered a risk factor for neuropsychiatric disorders, but the mechanisms involved in this process have not been completely elucidated. The aim of this study was to analyze the influence of hyperhomocysteinemia induction by methionine supplementation considering different levels and periods of exposure in mice. For this purpose, methionine supplementation at concentrations of 0.5 and 1% were administered in water to increase homocysteinemia in male C57BL/6 mice, and was maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
(56 reference statements)
3
14
0
Order By: Relevance
“…These results are consistent with the previous reports suggesting elevated Hcy levels in brain tissues following Hcy administration . A similar increase in Hcy levels was observed in cerebral cortex of animals following methionine‐induced HHcy . Hcy and H 2 S are both intermediates in methionine metabolism exerting opposite effects on neuronal cell viability .…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with the previous reports suggesting elevated Hcy levels in brain tissues following Hcy administration . A similar increase in Hcy levels was observed in cerebral cortex of animals following methionine‐induced HHcy . Hcy and H 2 S are both intermediates in methionine metabolism exerting opposite effects on neuronal cell viability .…”
Section: Discussionsupporting
confidence: 93%
“…In vitro studies demonstrated that addition of pro-oxidants to liver cell line increased conversion of homocysteine to cystathionine [29] and later to glutathione [42]. However, few studies have reported that glutathione content was unaltered in rats after methionine load [1,4]. The augmented hepatic oxidative stress measured as TBARS observed in the methioninefed group might also contribute to the activation of the transsulphuration pathway in our study.…”
Section: Discussionsupporting
confidence: 43%
“…Brain methionine concentrations were even significantly increased by 5.5-fold in PKU mice on LNAA supplementation compared to normal chow, corresponding with the similarly strong increases in blood. Although the cerebral and systemic effects and possible toxicity due to these strongly elevated methionine concentrations are not fully understood [ 36 ], at least these results warrant against indiscriminate supplementation of methionine in PKU. Also, brain histidine concentrations in PKU mice were even further increased on LNAA supplementation.…”
Section: Discussionmentioning
confidence: 99%